Comparison of Marginal Compliance and Microleakage of CL VRestorations in Deciduous Anterior Teeth Using Two Different RMGI Liners - Saeedeh Talebianpour; Hajar Attarzadeh (Isfahan University of Medical Sciences, 2022)
Microleakage has always been a problem in restorative dentistry. To decrease microleakage, differentrestorative techniques and materials have been recommended. The purpose of this study was to evaluate micro leakage of the composite restoration in deciduous anterior teeth using the open sandwich technique by two different liners.Materials & Methods:This cross-sectional experimental study was conducted at Khorasgan University in 2019. A total of sixty intact deciduous canine teeth were divided into 3 groups of 20. At the buccal surface of the specimens, the Class V cavity was extracted at 1 mm below the CEJ (Cementoenamel junction) and in groups 1 and 2, ionoseal liner and Fuji II ionomer glass were placed at the buccal floor. Cavities were restored with Z250 composite resin. In group 3 which served as the control, restorations was perfromed without liners. All samples are prepared for establishment after dying in methylene blue 0.5% solution. The buccal lingual incisions with a thickness of 1 mm were inspected under stereo microscope for micro leakage. A total of 5 samples were extracted from each group via random sampling to examine the marginal compliance under SEM (Scanning electron microscope). The intergroup comparisons were made using the chi-square and Kruskal-Wallis tests. Besides, intra-group comparisons were performed using the Mann-Whitney U test. All statistical procedures were performed at a significance level of less than 0.05 (p value < 0.05) using Gpower software.Results:The outcome of this study showed that microleakage of gingival margin in open sandwich techniques with ionoseal and Fuji II (group 1, 2) was significantly higher than in control group (p value = 0.033).but in comparison between group 1,2 there was no significant difference (p value = 0.795).In SEM evaluation there was no significant difference in gingival microleakage (p value = 0.232).Conclusion:Use of two liners: Ionoseal and Fuji II in Class V cavities restored by opensandwich technique in deciduce anterior teeth can reduce gingival microleakage.